Meta Analysis: Utilizing Problem-based Learning for Enhancing Creative Mathematical Thinking Abilities - Ernita, Ernita; Mariani, Scolastika; Agoestanto, Arief; Isnarto, Isnarto; Suyitno, Amin (FKIP Universitas Muhammadiyah Tangerang, 2024)
The ability to think creatively in a mathematical context is essential for students in the 21st century. In a global creativity survey carried out in 2015 by the Martins Prosperity Index, Indonesia was positioned 115th among 139 countries, with a score of 0.202, included in low category. One strategy to address this issue is by nurturing students' creative thinking skills in mathematics education. One exciting option for teaching is Problem-based Learning. This study aims to reevaluate how the Problem-based Learning approach can improve students' creative thinking skills in mathematics, building on existing research findings. The research method employed is meta-analysis, which involves the following steps; (1) formulate the topic; (2) overall study design; (3) sampling; (4) data collection; and (5) data analysis. Based on the results of the study, an average effect size of 1,057 was obtained in the high category. Meanwhile, based on the t-test enhancement test, obtained t_value=17,020≥t_table=1,648. In conclusion, the average performance of classes utilizing Problem-based Learning is higher than that of classes using other models. The further research is needed regarding the application of Problem-based Learning to cube and cuboid material at junior high school level because the related research is the only research reviewed that has a medium effect size value